NONPARAMETRIC STABILITY ANALYSIS OF YIELD FOR NINE CHILI PEPPER (Capsicum annuum L.) GENOTYPES IN EIGHT ENVIRONMENTS - Rahadi, Vitria Puspitasari; Syukur, Muhamad; Sujiprihati, Sriani; Yunianti, Rahmi (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2013)
The objectives of this study were to compare nonparametric stability measures, and to identify promising high yield and stability of chili pepper (Capsicum annuum L.) genotypes in eight environments. In every environment, a Randomized Complete Block Design was used with three replications. The method of Nassar and Huehn, Kang, Fox, and Thennarasu was used to analyze the stability and high yield. Spearman’s correlation and Principal Component analysis distinguishes the methods based on two different concepts of stability: the static (biological) and dynamic (agronomic) concepts. The top method was found to be the dynamic stability. Meanwhile, the methods of Si1, Si2, Si3, Si6, Npi1, NPi2, NPi3 and NPi4 were found to be the static stability. Based on the ranking frequency stability of the nonparametric method, the genotypes with the highest frequency of static stability ranking were genotypes IPB002003, IPB002046, IPB009019 and Tit Super, whereas IPB009002 and Tombak were categorized as those of dynamic stability. Genotype IPB120005 and IPB019015 were less adaptable in the multiple environments tested. It shows that the genotypes were specific in certain environments. IPB120005 had high yield and specific location in Boyolali in dry season and IPB019015 genotype was specific in Bogor in wet season. Keywords: chili pepper, nonparametric stability, high yield, dynamic stablility